Pemodelan dan Simulasi Gerakan Rotor Motor Stepper Jenis Variable Reluctance 3-Fasa Berbasis MATLAB/Simulink - Budhi Anto (Universitas Syiah Kuala, 2012)
This paper presents MATLAB/Simulink based modelling and simulation of rotor motion of 3-phase variable reluctance stepper motor to show electromechanical conversion process inside the motor when electricity fed to the motor. Stator part of the motor has a pair of salient pole per phase and rotor part has 8 teeth. Stator windings are wound around stator salient poles, while rotor part has no windings. Simulation process is started by the work to derive rotor motion equation based on stepper motor construction data using energy in coupling field method, then the equation is simulated using MATLAB/Simulink program. Simulating by variation of stator current frequency shows rotor part of the stepper motor rotates in 15 degree steps for any variant of stator current frequency.